PROFESIONALISME POLISI LALU LINTAS DALAM PENANGGULANGAN KECELAKAAN LALU LINTAS (Studi Pada Satuan Lalu Lintas Kepolisian Resor Kota Padang) - Dian Jumes Putra (Program Magister Ilmu Hukum Universitas Ekasakti, 2019)
Law Number 22 Year 2009 concerning Road Traffic and Transportation is intended torealize security and safety and order in traffic. Empirical facts show that the legalcompliance of people in traffic on the highway is decreasing. Many road users do notcomply with traffic regulations, so that traffic accidents on the road that tend to increaseThe high number of traffic accidents must be handled by the police professionally byhandling accidents based on the established standard operating procedures.